Northern Bobwhite Densities in Burned and Unburned Redberry Juniper Rangelands - Anthony P. Leif; Loren M. Smith (National Quail Symposium Proceedings, 2017)
We estimated northern bobwhite (Colinus virginianus) densities in 4- and 8-year-old burned and unburned redberry juniper (Juniperus pinchottii) dominated pastures. The 4-year-old burned (800 ha), 8-year-old burned (1,200 ha), and unburned (1,200 ha) treatment sites had 8.6, 14.4, and 22.3% woody canopy coverage, respectively. Fall bobwhite densities were estimated from 122 flushes of quail coveys on 592.8 km of transects. Data histograms indicated that bobwhite were harder to detect in the unburned area than in the 8-year-old burn or the 4-year-old burn. Probability detection functions were smaller in the old burn than the new burn (P = 0.05) or unburned area (P = 0.02). Bobwhite densities of 43.3, 55.1, and 60.5 birds/100 ha in the 4-year-old burn, 8-year-old burn, and unburned sites, respectively, were similar (P > 0.10). Prescribed burning to control redberry juniper and manage bobwhite should be designed to maintain intermittent shrub coverage.
Keywords: Colinus virginianus; densities; line transects; northern bobwhite; prescribed burning; rangeland; Texas